2009
DOI: 10.2105/ajph.2007.116103
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status and Body Mass Index Among Hispanic Children of Immigrants and Children of Natives

Abstract: The positive income-BMI association among Hispanic immigrant children might reflect cultural differences that immigrant parents carry with them from their countries of origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 22 publications
4
45
0
Order By: Relevance
“…Possible risk factors for early childhood weight disparities among Latinos compared to Whites—stemming from our analysis and earlier research—include low maternal education, higher rates of maternal depression, early introduction of solid foods, restrictive feeding practices, physical inactivity, and beverage and fast food consumption patterns [4, 5, 31, 32]. In addition, these findings support theories which suggest Latino immigrant families may face rapid increases in income which when combined with indulging cultural feeding practices and easy accessibility to processed foods, which are often inexpensive and highly caloric, may contribute to unhealthy weight development [25, 33]. Additional research methodologies are needed to build on the etiologies of weight development in Latino children; however, it is clear that Latino children, particularly from primary Spanish-speaking households, may benefit from targeted efforts on known risk factors in order to reduce these early weight disparities and promote healthy weight development.…”
Section: Discussionmentioning
confidence: 76%
“…Possible risk factors for early childhood weight disparities among Latinos compared to Whites—stemming from our analysis and earlier research—include low maternal education, higher rates of maternal depression, early introduction of solid foods, restrictive feeding practices, physical inactivity, and beverage and fast food consumption patterns [4, 5, 31, 32]. In addition, these findings support theories which suggest Latino immigrant families may face rapid increases in income which when combined with indulging cultural feeding practices and easy accessibility to processed foods, which are often inexpensive and highly caloric, may contribute to unhealthy weight development [25, 33]. Additional research methodologies are needed to build on the etiologies of weight development in Latino children; however, it is clear that Latino children, particularly from primary Spanish-speaking households, may benefit from targeted efforts on known risk factors in order to reduce these early weight disparities and promote healthy weight development.…”
Section: Discussionmentioning
confidence: 76%
“…Other studies reported in the literature have shown similar conflicting results. [53][54][55] Psychosocial Stress Psychosocial stress has been identified as a possible factor contributing to childhood obesity. Psychosocial stress may result from a child's school, family, or other interpersonal environments they encounter daily.…”
Section: Sleepmentioning
confidence: 99%
“…[14][15][16][17][18][19] Preadolescent Hispanic immigrant children weigh more than children born in the United States, [20][21][22][23] and ethnic-minority immigrant children are at higher risk of childhood obesity than comparable nativeborn children. [24][25][26] Obesity rates increase as children grow older, 15 and age is the single largest predictor of obesity in children.…”
Section: Demographic and Economic Characteristicsmentioning
confidence: 99%